TECHNOLOGIES FOR DEVELOPMENT OF CREATIVE COMPETENCE OF FUTURE TEACHERS (American Journal of Interdisciplinary Research and Development, 2023)
This article talks about innovative forms of teaching, tools for creativity development, modern creative methods proposed for use in lectures and practical training in the development of creative competence of future teachers.